2009
DOI: 10.1007/s10529-009-9952-1
|View full text |Cite
|
Sign up to set email alerts
|

1,3-Diferuloyl-sn-glycerol from the biocatalytic transesterification of ethyl 4-hydroxy-3-methoxy cinnamic acid (ethyl ferulate) and soybean oil

Abstract: 1,3-Diferuloyl-sn-glycerol is found ubiquitously throughout the plant kingdom, possessing ultraviolet adsorbing and antioxidant properties. Diferuloyl glycerol was synthesized and isolated as a byproduct in up to 5% yield from a pilot plant scale packed-bed, biocatalytic transesterification of ethyl ferulate with soybean oil or mono- and diacylglycerols from soybean oil. The yield of the diferuloyl glycerol byproduct was directly proportional to the overall water concentration of the bioreactor. The isolated d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 27 publications
1
12
0
1
Order By: Relevance
“…However, lipase-mediated direct esterification of p-hydroxycinnamic acids (60-70) with alcohols generally suffers from long reaction time and/or low yields. To improve the efficiency of this reaction, one can either reduce the conjugated unsaturation (via catalytic hydrogenation) (65,(70)(71)(72)(73)(74)(75), use alkyl p-hydroxycinnamates (e.g., ethyl, n-octyl) (70,73,(75)(76)(77)(78)(79)(80)(81)(82)(83) or ionic liquids as solvents (68,84,85). Therefore, to warrant high yields transesterifications with the selected primary and/or secondary alcohols (i.e., ethylene glycol, 1,3-propanediol, 1,4-butanediol, isosorbide, and glycerol), the initial step of our synthetic approach was the production of ethyl dihydroferulate (2).…”
Section: Chemo-enzymatic Synthesis Of a New Class Of Renewable Polyphmentioning
confidence: 99%
“…However, lipase-mediated direct esterification of p-hydroxycinnamic acids (60-70) with alcohols generally suffers from long reaction time and/or low yields. To improve the efficiency of this reaction, one can either reduce the conjugated unsaturation (via catalytic hydrogenation) (65,(70)(71)(72)(73)(74)(75), use alkyl p-hydroxycinnamates (e.g., ethyl, n-octyl) (70,73,(75)(76)(77)(78)(79)(80)(81)(82)(83) or ionic liquids as solvents (68,84,85). Therefore, to warrant high yields transesterifications with the selected primary and/or secondary alcohols (i.e., ethylene glycol, 1,3-propanediol, 1,4-butanediol, isosorbide, and glycerol), the initial step of our synthetic approach was the production of ethyl dihydroferulate (2).…”
Section: Chemo-enzymatic Synthesis Of a New Class Of Renewable Polyphmentioning
confidence: 99%
“…According to the previous reports [7,11,13], FGs can be prepared by chemical and enzymatic methods. Owning to the elevated temperatures, non-enantioselectivity, and pollution [12,14,15], chemical synthesis of FGs was limited.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with chemical methods, enzymatic synthesis of FGs showed many performances, such as, mild reaction conditions, high catalytic efficiency, high enantioselectivity, and low energy consumption [7,9,10]. However, in the previous enzymatic synthesis of FGs, excess glycerol or organic solvents were required as reactants and solvents to obtain high FGs yields [9,13,15,16]. To overcome these disadvantages, ionic liquids (ILs), due to their negligible vapor pressure, high thermal stability for enzyme, and favorable solvating property (molecular sieve role) for particular components [17][18][19][20][21], have been used as an alternative green reaction medium for many enzymatic reactions.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Laszlo, Compton, Eller, Taylor, and Isbell () demonstrated that feruloylated monoacyl‐ and diacylglycerols have excellent ultraviolet A and B absorbing properties, and Compton, Laszlo, and Evans () prepared that 1‐feruloyl‐ sn ‐glycerol (FG) and 1,3‐diferuloylglycerol (F 2 G) had free radical scavengers and peroxyl radical inhibitors. Karboune, Saint‐Louis, and Kermasha () prepared conjugates of cinnamoylated lipids and 2,2‐diphenyl‐1‐picrylhydrazyl (DPPH) that possessed higher free radical scavenging activities than the corresponding phenolic acids (Compton & Laszlo, ). To the best of our knowledge, the antioxidant effects of 1‐caffeoylglycerol (1‐CG) have not yet been reported.…”
Section: Introductionmentioning
confidence: 99%